Effects of increasing hominy feed in diets on finishing pig performance - Potter, M. L.; Jacela, J. Y.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,035 finishing pigs (initially 79.4 lb) were used in an 84-d growth trial to evaluate the effects of increasing hominy feed on finishing pig growth performance. Pens of pigs were blocked by average initial pig BW and randomly allotted to 1 of 4 dietary treatments (10 pens per treatment) with initial weights balanced across the treatment groups. Treatments were increasing levels (0%, 12.5%, 25%, and 37.5%) of corn hominy feed added to a corn-soybean meal-based diet. All treatment diets were fed in 4 phases, and hominy feed inclusion was constant among phases. Increasing hominy feed resulted in a linear decrease (P < 0.01) in ADG and ADFI from d 0 to 84. Regardless of treatment, there was no difference (P > 0.35) in F/G. The lower feed consumption and poorer growth performance resulted in pigs fed diets containing any level of hominy feed weighing less than pigs fed standard corn-soybean meal-based diets at the end of the trial. These data indicate that adding corn hominy feed as an alternative ingredient in swine diets is a viable option; however, a decrease in performance should be considered when deciding if it is cost-effective to include hominy feed in finishing diets.
Keywords: Alternative ingredient; Hominy feed; Growth; Swine